2017
DOI: 10.1016/j.vaccine.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Improving adolescent HPV vaccination in a randomized controlled cluster trial using the 4 Pillars™ practice Transformation Program

Abstract: Objective Uptake of meningococcal vaccine (MCV) and tetanus, diphtheria and pertussis (Tdap) vaccine among adolescents has approached Healthy People 2020 goals,[1] but human papillomavirus (HPV) vaccination has not. This study evaluated an intervention using the 4 Pillars™ Practice Transformation Program to increase HPV, MCV and Tdap uptake among adolescents in primary care practices. Methods Practices with at least 50 patients 11–17 years old with estimated vaccination rates less than national goals, were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 36 publications
(40 reference statements)
1
46
0
Order By: Relevance
“…These increases were higher than 10 PP increases in HPV initiation and 13 PP increases in HPV completion rates previously reported in the RCCT, in which these sites were the control group. 11 This may be explained in part, by the longer follow-up period in this study, as well as the significant HPV initiation increases observed among these practices during the RCCT. Having already increased the number of adolescents receiving the first or second dose of HPV in effect, gave these practices a year-long period in which to complete the remaining doses of the 3-dose series.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…These increases were higher than 10 PP increases in HPV initiation and 13 PP increases in HPV completion rates previously reported in the RCCT, in which these sites were the control group. 11 This may be explained in part, by the longer follow-up period in this study, as well as the significant HPV initiation increases observed among these practices during the RCCT. Having already increased the number of adolescents receiving the first or second dose of HPV in effect, gave these practices a year-long period in which to complete the remaining doses of the 3-dose series.…”
Section: Discussionmentioning
confidence: 80%
“…The sample size in this study precludes analyzing the effectiveness of specific strategies; however, in the RCCT related to this study, significant increases in vaccine uptake were related to adoption of >10 strategies. 6 Combinations of provider- and patient-based strategies may address previously observed barriers to HPV vaccination among adolescents. 1418 Despite a Pennsylvania state mandate 19 for children to receive meningococcal and Tdap vaccines at ages 11–12 years, pre-intervention vaccination rates among participating practices were below 2015 Pennsylvania and U.S. averages (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Created by researchers at the University of Pittsburgh, this program has been used by over 50 primary care offices and focuses on 4 domains: convenience, communication, facilitation, and motivation. 56 In 2013, the inventors of program partnered with the Immunization Action Coalition (IAC) and conducted a randomized, cluster trial of 20 primary care practices with at least 50 11-17 y old patients. After 9 months of program implementation at intervention sites, HPV series initiation rates increased 10.2 percentage points vs. 7.3 in control sites (p < 0.001 for difference).…”
Section: Health-system Initiativesmentioning
confidence: 99%